Idoso dependente: representações do cuidador familiar sobre o cuidar - Silva, Marta Lucia Souto da (2011)
This research on dependent elderly arises from a visible observation of the increasing number of elderly under chronic diseases and functional dependence, what results in the need of a caretaker assistance which, most of the times, a family member undertakes. This research aims at analyzing the representation of the family caretaker on the dependent elderly caring, using a qualitative approach methodology. The field research developed in a Basic Health Unit with the Family Health Strategy belonging to the Santa Marcelina Health Social Organization of the Eastern Small Region Guaianases. The study population consisted of 10 dependent elderly and their respective family caretakers. Through a questionnaire named "Knowing the dependent elderly and his/her caretaker", data of identification was collected and complemented with semi- structured interviews and the use of guided questions on caretaker representations. The analysis showed that 50% of the elderly had Cerebral Vascular Accident as the trigger for the need of a caretaker. It was evident that 90% were female caretakers, frequently his/her own daughters, and that difficulties are present concerning residence infrastructure to provide such assistance, what most of the times can even interfere negatively in the daily routine of the elderly and his/her caretaker. The conflicts among relatives regarding the caring attribution to the family members, could be also observed in the results reached, demonstrating the need for more and more qualified interventions from the Family Health Strategy